Characterization of axial compressor performance at locked rotor and torque-free windmill conditions - Ferrer-Vidal, Luis E.; Iglesias-Pérez, Alejandro; Pachidis, Vassilios (Elsevier, 2020)
Prediction of aero-engine performance in the sub-idle regime is becoming increasingly important. Performance prediction tools rely on component maps to enable system-level simulations. Methods to obtain compressor sub-idle maps have traditionally relied on low-order extrapolations, but the continued development of robust turbomachinery numerical methods suggest that these tools may be sufficiently robust to allow improved performance predictions at these challenging off-design conditions. In this work, an axial compressor rig is used to obtain locked rotor and windmill performance characteristics which are then compared against results from Computational Fluid Dynamics (CFD) simulations. This paper assesses the capability of steady state RANS CFD as a tool for the prediction of sub-idle compressor performance and helps delineate the minimal modelling fidelity required to obtain sufficiently accurate performance models. The multi-stage performance of axial compressors at locked rotor and at the zero-torque windmilling condition are discussed. Windmilling multi-stage compressors are found to operate with the front stages compressing the flow and the last stages expanding to satisfy the power balance. The torque-free windmilling behavior of axial compressors can be described non-dimensionally, allowing limited numerical simulations to be used to build sub-idle performance models.
Keywords: Characteristics; Sub-idle; Windmilling; URANS; RANS; CFD; Compressor